Investigating the regulation of DNA and RNA modifications in neurocognitive diseases - Perez Grovas Saltijeral, Adriana (2025)
Dementia is a leading cause of disability in the elderly, with over 55 million people diagnosed worldwide as of 2019. Neurodegenerative dementias result from the progressive and irreversible degeneration of neurons. Epigenetic and epitranscriptomic processes regulate transcriptional and translational activities, mediating gene expression and environmental influences on cell physiology. Such processes are tissue and cell-type specific, change during cellular differentiation and ageing, and are increasingly relevant in understanding disease-modifying mechanisms. Chemical modifications on DNA and RNA, such as methylations, are governed by three families of effector proteins known as writers, readers and erasers. The expression of these DNA and RNA modifications and their effector proteins across brain regions and within cellular environments significantly impacts transcription and translation activities, leading to disease.